Avaliação e regulação da educação a distância no ensino superior brasileiro: um olhar sobre os processos de credenciamento institucional - Lobo, Márcia Eunice (2011)
Just after the Policy and Foundations of National Education Law (LDB) publication, it was started in Brazil, a perceivable growing in the offering of face-to-face undergraduate courses and, in the years that followed, there was an exponential growth in distance learning programs, offered by higher education organizations, public and private, authorized to such offering. Such organizations should submit, at least, two different and complementary processes for approval: an institutional authorization process for distance education and a specific process for each undergraduate course to be offered through distance learning. There was a clear and recurring oscillation in the evaluation forms used in such processes and also a search for a unique definition for distance education in higher education, which should consider theoretical and methodological approaches, policies and all the rules for distance education. In such scenario, this thesis is the result of a research about distance education on Brazilian higher education, focusing on regulation and evaluation. Starting from the epistemological fundamental principles of authors, three different and complementary approaches are displayed: humanist, technicist and economicist. Such theoretical assumptions contribute in order to ground the research. The policies, technology and distance education concepts are also presented in a dialectic way, aiming to corroborate the interdependence between policy and technology. The main goals of this work are to analyze the oscillations in regulation, from 1996 until 2010, as a consequence of explicit policies in evaluation forms; and also to answer under which fundamentals were elaborated the evaluation forms for institutional authorization process and courses authorization, specifically for distance learning undergraduate courses. It is made through the search of a relationship between indicators, fundamentals and policies, and analysis categories, which are kept in the evaluation documents and in the specific. Finally, some reflections are made, matching the authors to the legal foundations, the policies to the practical experience as a researcher for more than fourteen years in the field of distance education